Mechanisation of small-scale farms in South Asia: Empirical evidence derived from farm households survey - Aryal, Jeetendra P; Rahut, Dil B; Thapa, Ganesh; Simtowe, Franklin (Elsevier, 2021)
In the agricultural sector, labour shortage, and increase in wages resulting from out-migration, and the necessity to employ sustainable intensification practices to minimise the use of inputs such as water, fertilizer, and energy, calls for investment in the mechanisation of small-scale farms in South Asia (SA). Therefore, this study investigates the mechanisation process undertaken in SA with a special reference to India, Nepal, and Bangladesh, where agriculture, an important source of rural livelihoods, is adversely affected by out-migration and the depletion of natural resources. This study finds that tractors (74%), pumps (72%), threshers (65%), harvesters (23%), and power tillers (16%) are the predominantly used farm machinery in SA. Farm mechanisation is most widespread in India, followed by Nepal and Bangladesh, though the types of machinery used vary across them. Multivariate probit model shows that male headship, access to credit and extension services, economic status, and training positively influence farm mechanisation. Hence, along with enhanced provision for credit and training, an agricultural policy that aims to improve access to farm machinery should target marginalised and poor farmers to sustain agricultural production and ensure food security.